Rethinking administrative documents’ validity to cutoff greenhouse gas emissions by million tons - Moustafa, Khaled (Jurnal Rekayasa Proses, 2023)
Climate change is a multi-hazard challenge for life on earth in all its aspects. Wildfires, pollution, drought and heatwaves are just a few examples of exacerbated environmental crises propelled by climate change effects. To mitigate such effects, urgent actions are required to cutoff greenhouse gas emissions by all the means across all the sectors. Every additional kilogram of greenhouse gases produced unnecessarily should be avoided. One source of greenhouse gas emissions that may not be top of mind for the public and policymakers - and which can be taken into account in preventive environmental policies- is the industry of administrative and identification documents (papers) with short validity dates that involves intensive production (mass printing) and frequent renewals (mass reprinting) while the carbon footprint is too high. The validity of, for example, identity cards, passports, banking cards, driving licenses, etc., is often short ranging from ~ 3 to 10 years, depending on each type of document and issuing country. Short validity dates, however, should raise critical questions regarding the environmental sustainability, societal and carbon impact, and depletion of natural resources used in their production and frequent renewals. Identification documents are not food products that spoil over time or medications that lose their functional activities, so their validity should be unlimited by time in order to avoid the high environmental costs of mass printing/reprinting and high rates of greenhouse gas emissions associated with their production. The production of plasticized ID-type cards can emit up to 100 grams of carbon dioxide equivalent per card. Manufacturing one administrative document per person and renewing it five times could produce up to 4 million tons of carbon dioxide globally. If individuals have five administrative documents that need renewing five times, which is often the case, gas emissions would be five times higher, or approximately 20 million tons of CO2 equivalent. To save such important amounts of gas emissions, a modernization and flexibilization of administrative documents industry is required toward removing validity by date. This simple change could save substantial amounts of energy and natural resources, such as trees and water, while also reducing greenhouse gas emissions by million tons, especially in the pressing context of climate change. It should be time to initiate a paradigm shift in the administrative document industry. Eliminating validity periods is a straightforward yet effective solution that would significantly reduce greenhouse gas emissions and promote sustainable environmental practices.